Down-Regulation of CXXC5 De-Represses MYCL1 to Promote Hepatic Stellate Cell Activation - Wu, Xiaoyan; Dong, Wenhui; Xu, Huihui; Ren, Haozhen; Wang, Jinglin; Shang, Longcheng; Zhu, Zhengyi; Zhu, Wei; Shi, Xiaolei; XU, YONG (Frontiers in Cell and Developmental Biology, 2021)
Liver fibrosis is mediated by myofibroblasts, a specialized cell type involved in wound healing and extracellular matrix production. Hepatic stellate cells (HSC) are the major source of myofibroblasts in the fibrotic livers. In the present study we investigated the involvement of CXXC-type zinc-finger protein 5 (CXXC5) in HSC activation and the underlying mechanism. Down-regulation of CXXC5 was observed in activated HSCs compared to quiescent HSCs both in vivo and in vitro. In accordance, over-expression of CXXC5 suppressed HSC activation. RNA-seq analysis revealed that CXXC5 influenced multiple signaling pathways to regulate HSC activation. The proto-oncogene MYCL1 was identified as a novel target for CXXC5. CXXC5 bound to the proximal MYCL1 promoter to repress MYCL1 transcription in quiescent HSCs. Loss of CXXC5 expression during HSC activation led to the removal of CpG methylation and acquisition of acetylated histone H3K9/H3K27 on the MYCL1 promoter resulting in MYCL1 trans-activation. Finally, MYCL1 knockdown attenuated HSC activation whereas MYCL1 over-expression partially relieved the blockade of HSC activation by CXXC5. In conclusion, our data unveil a novel transcriptional mechanism contributing to HSC activation and liver fibrosis.